2005
DOI: 10.1121/1.1854312
|View full text |Cite
|
Sign up to set email alerts
|

Integration and segregation in auditory scene analysis

Abstract: Assessment of the neural correlates of auditory scene analysis, using an index of sound change detection that does not require the listener to attend to the sounds [a component of event-related brain potentials called the mismatch negativity (MMN)], has previously demonstrated that segregation processes can occur without attention focused on the sounds and that within-stream contextual factors influence how sound elements are integrated and represented in auditory memory. The current study investigated the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 53 publications
6
90
1
Order By: Relevance
“…The regularities stored in memory provide the auditory context from which deviance detection takes place. Thus, the representation of sounds in memory (e.g., as one or two streams) forms the basis for evaluating incoming sound information (Sussman, 2005;Sussman and Steinschneider, 2006). Deviance detection is determined on the basis of the stored regularities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regularities stored in memory provide the auditory context from which deviance detection takes place. Thus, the representation of sounds in memory (e.g., as one or two streams) forms the basis for evaluating incoming sound information (Sussman, 2005;Sussman and Steinschneider, 2006). Deviance detection is determined on the basis of the stored regularities.…”
Section: Discussionmentioning
confidence: 99%
“…The MMN, which is generated bilaterally within auditory cortices (Alho, 1995;Giard et al, 1990), reflects the output of a deviance detection process. The deviance detection process is based upon the extraction of regularities ('standard') within the auditory input, from which detected violations ('deviants') elicit MMN as a result of a comparison process (Näätänen et al, 2001;Sussman, 2005). Thus, MMN can be used to determine which regularities (individual features or pattern of sounds) are represented in sensory memory at the time the 'deviant' occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results (Carlyon, 2004;Cusack et al, 2004;Wrigley and Brown, 2004;Molholm et al, 2005, Snyder et al 2006) also suggest the presence of two cortical mechanisms of streaming -an automatic "pre-attentive" segregation of sounds and an attention-dependent streaming mechanism. The process of auditory scene analysis sets the stage and seamlessly interacts with the auditory attention system (Naatanen et al, 2001;Opitz et al, 2005;Sussman, 2005). Thus, an explanation of the cocktail party effect must include an understanding of the interplay between ASA, and our abilities to direct spatial attention to sound sources within the acoustic scene and/or to direct featural attention by focusing on distinctive acoustic vocal features (such as fundamental frequency, timbre, accent, intonation) in order to identify individual speaker voices (Ahveninen, et al, 2006).…”
Section: I2 Brief Review Of Auditory Attentionmentioning
confidence: 99%
“…Sussman (2005) 28 analyzed the auditory aspect by means of a sound change detection sequence (MMN). He showed that the segregation processes can occur without attention focused in the sounds and how the sound elements are integrated and represented in the auditory memory.…”
Section: Mismatch Negativity (Mmn)mentioning
confidence: 99%